ANALISIS PERILAKU SEKTOR PERTANIAN INDONESIA: APLIKASI VECTOR ERROR CORRECTION MODEL - Andi Irawan (Jurnal Manajemen & Agribisnis, 2005)
The specific goals of this study were:Firstly, in the long run perspective, the goal is to analyze impact of policythat inflate agriculture price to growth, employment, and investment inagriculture sector. Secondly, in the short run perspective, the goals are: (1)to analyze which economic blocks that have most producing instability toagriculture sector, (2) to analyze behaviour af inflation in agriculture sectorand causality relationship both among output price and input prices and amonginput prices. Quantitative methods used ini this studywere Vector Error Correction Model, Johansen Cointegration Test, and GrangerCausality Test. Data used in this study come from several sources such as BankIndonesia, BPS Statistic, International Financial Statistic and CEIC dataCompany Limited, series data from first monthly of 1993 (1993:01) up to thelast monthly of 2002 (2002:12). In the agriculture sector, production(output) and capital are responsive to change in the output price. This meanthat inflating the output price effectively help generate output and newinvestment in this sector. Nevertheless because shock in price can be source ofinstability to agriculture sector, so government should be carefully applypolicies that can inflating the price in agriculture. To solve unemploymentproblem in agriculture sector, government should apply cost strategy such assubsidy policy of input price.